A Novel Highly Efficient Device for Growing Micro-Aerophilic Microorganisms - Fuduche, Maxime; Davidson, Sylvain; Boileau, Céline; Wu, Long-Fei; Combet-Blanc, Yannick (Frontiers in Microbiology, 2019)
This work describes a novel, simple and cost-effective culture system, named the Micro-Oxygenated Culture Device (MOCD), designed to grow microorganisms under particularly challenging oxygenation conditions. Two microaerophilic magnetotactic bacteria, a freshwater Magnetospirillum gryphiswaldense strain MSR-1 and a marine Magnetospira sp. strain QH-2, were used as biological models to prove the efficiency of the MOCD and to evaluate its specifications. Using the MOCD, growth rates of MSR-1 and QH-2 increased by four and twofold, respectively, when compared to traditional growing techniques using simple bottles. Oxystat-bioreactors have been typically used and specifically designed to control low dissolved oxygen concentrations, however, the MOCD, which is far less sophisticated was proven to be as efficient for both MSR-1 and QH-2 cultures with regard to growth rate, and even better for MSR-1 when looking at cell yield (70% increase). The MOCD enables a wide range of oxygenation conditions to be studied, including different O2-gradients. This makes it an innovative and ingenious culture device that opens up new parameters for growing microaerobic microorganisms.